Strategi Pengenalan Program Microsoft Word Siswa SDN Pamotan 2 Desa Pamotan Kabupaten Lamongan - Riska Ayu Eliana; Muhammad Arif Ananto; Nurkalila Hasna; Arini Imandasari; Arda Farhadina Sartika; Andi Dwi Prasetyo; Susan Orain; Riantiza Amartya Nurlika; Luluk Fajar Sari; Helda Urbhani Rosa; Dwi Yuli Pujiastuti (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRAK Perkembangan teknologi informasi yang pesat di era globalisasi tidak bisa dihindari lagi pengaruhnya di dalam dunia pendidikan. Dunia pendidikan dituntut untuk senantiasa menyesuaikan diri dengan perkembangan teknologi informasi dan komunikasi. Salah satu perkembangan teknologi informasi dan komunikasi adalah berkembangnya komputer dan program-program di dalamnya. Namun, pembelajaran menggunakann komputer belum merata terutama di sekolah pedesaan yang fasilitasnya masih terbatas. Tujuan dari Pengenalan Microsoft Word ini adalah meningkatkan pengetahuan dan ketrampilan siswa/I dalam penggunaan komputer terutama pada program Micorosft Word. Sasaran kegiatan ini adalah siswa/I sekolah dasar Pamotan II kelas 4,5, dan 6, Desa Pamotan, Kecamatan Sambeng, Kabupaten Lamongan. Metode yang digunakan adalah dengan memberikan pelatihan dasar-dasar dan pengoperasian Microsoft Word. Hasil dari kegiatan ini adalah siswa/I mampu mengetahui dan mengoperasikan Microsoft Word secara mandiri. Kesimpulan dari kegiatan ini adalah pengetahuan dan ketrampilan siswa/I meningkat setelah adanya pelatihan ini. Kata Kunci: Pendidikan, Microsoft Word, Sekolah Dasar  ABSTRACT The rapid development of information technology in the era of globalization cannot be avoided anymore its influence in the world of education. The world of education is required to constantly adapt to the development of information and communication technology. The government has imposed a large-scale social restriction (PSBB) policy to reduce the spread of the epidemic, so that all activities outside the home must be stopped until the Covid-19 pandemic subsides. As a result, the process of teaching and learning activities must be carried out online from their respective homes in order to minimize the spread of Covid-19. Learning to use computers has not been evenly distributed, especially in rural schools whose facilities are still limited. The purpose of this introduction to Microsoft Word is to improve students' knowledge and skills in using computers, especially in the Microsoft Word program. The targets of this activity are students of Pamotan II elementary school grades 4,5, and 6, Pamotan Village, Sambeng District, Lamongan Regency. The method used is to provide basic training and operation of Microsoft Word. The result of this activity is that students are able to know and operate Microsoft Word independently. The conclusion of this activity is that the students' knowledge and skills increased after this training. Keywords: Education, Microsoft Word, Elementary School